Boron concentrations in tap water in many cities of Turkey - YARAT, AYŞEN (TAYLOR & FRANCIS LTD, 2020)
Boron concentrations in 335 tap water samples collected from 75 cities in Turkey have been determined by inductively coupled plasma-mass spectrometry. Boron levels ranged between 0.001 and 5.5 mg/L. The lowest boron levels were in Trabzon, the highest in Kayseri. Boron levels in tap water from cities of the Aegean, Eastern, and Central Anatolian Regions were higher than those from cities of the Marmara, Black Sea, South East, and Mediterranean Regions. The overall mean value was around 0.2 mg/L, lower than the limit levels given by the WHO and the European Union, and also the limit level established by Turkish regulations. In some cities, these limit values were exceeded, generally in the tap water of cities where the drinking water based on groundwater or of those located in the vicinity of hot springs, volcanic areas, or boron production regions. This is the most detailed study evaluating boron levels in the drinking water of Turkey. To conclusion, since the boron intake is being mainly with nutrients and drinking water it may effect public health. To know boron levels in drinking waters is also very important for epidemiologic studies and for establishment of database of boron level in drinking waters in Turkey. [GRAPHICS] .
Keywords: Boron; drinking water; ICP-MS; trace elements; Turkey; DRINKING-WATER; DIETARY BORON; CONTAMINATION; HEALTH